Bioactive porous ZrO2-based ceramics with a hierarchical porosity for artificial bone scaffolds. (1st May 2023) - Wang, Bohan; Yu, Wenjun; Fu, Le
Abstract: Given the pressing clinical need, the market for artificial bone scaffolds in orthopedics is growing at a rapid rate. In the past, ZrO2 -based biomaterials intended for implantation were dense and 'bio-inert'. Material scientists have now shifted toward the design of deliberately porous and 'bioactive' ZrO2 -based biomaterials that integrate with human cells and tissues. In this study, we designed and prepared porous and bioactive ZrO2 –SiO2 nanocrystalline ceramics. The phase composition, microstructure, pore formation mechanism, and ion release behaviors of the ceramics were explored. The ceramics showed a hierarchical porosity, consisting of connected macropores (∼100 μm or larger) and micropores (∼1 μm). The spherical macropores were formed by a pore-forming agent method, and the irregular micropores were formed because of incomplete densification. The bioactive dopants (Ca and Sr) acted as a destabilizer of tetragonal ZrO2 . Ca, Si, and Sr ions continuously released from the surface of the samples, providing good bioactivity for the ceramics. The porous and bioactive ceramics show great potential to be used as artificial bone scaffolds.